Research on the recycled and hybrid fibre reinforced self-compacting concrete under flexure - Pająk, Małgorzata (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
In the present study the steel fibres coming from the end-of-life tires were applied as a reinforcement of self-compacting concrete. The influence of the recycled fibres and their mixture with glass or polypropylene fibres (hybrid mixes) on the flexural behaviour of SCC was tested. The research revealed that the dosage of 1.5% of recycled fibres is highly effective in the SCC matrix. The values of the residual flexural tensile strengths obtained in the tests classified the R-SCC to be used as a partial replacement of the conventional reinforcement. The addition of other types of fibres to R-SCC caused the further enhancement of flexural parameters with no negative effect on the distribution of the fibres in the mix.